Persepsi Guru Terhadap Penerapan Kurikulum 2013 di Kabupaten Majene - Ana Muliana Musli (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2017)
This study aimed to determine the extent to which Curriculum 2013 improved learning process in classroom compared to KTSP 2006 according to teachers’ perceptions. In addition, this study aimed to determine the teachers’ response to this new curriculum as well as to find out what difficulties they face in relation to the implementation of this curriculum in school. This research was combine quantitative research and qualitative research. This research used sequential explanatory design where the first phase used quantitative method and the second phase used qualitative method. As a data-gathering instrument, questionnaires and direct interviews were used to find out more about teachers' perceptions about curriculum 2013. To make the scope less extensive, this study was limited to math teachers in the upper secondary school. The samples in this study were two Senior School and two Vocational School, namely SMAN 1 Majene, SMAN 3 Majene, SMKN 2 Majene and SMKN 5 Majene. From the quantitative research, it is found that in general, teachers’ response to curriculum 2013 is positive, with the total average value is 3.82 and is in agreed category range. While from the qualitative research, it is found that in implementation of curriculum 2013 in schools teachers get some obstacles such as their student lack of readiness with the learning model in the curriculum, incomplete facilities and infrastructure, and lack of socialization about the curriculum. Meanwhile, from the credibility test results, it is found that the constraints arise from the imbalance between the terms of implementation of curriculum 2013 with the real conditions. To work around this, teachers made casuistic adjustments in the implementation of this curriculum.